High-quality-factor Fano resonance and tunable light absorption based on diagonal circles of the bound state in the continuum - Jicheng Wang; Shu-Wen Cui; Wenjie Shi; Zheng-Da Hu; Lin Yu (Results in Physics, 2022)
This study proposes a novel metasurface structure made of dielectric diagonal round holes. It is possible to achieve the quasi-bound state in the continuum (quasi-BIC) resonance modes with high Q-factors by introducing symmetry breaking into the unit structure. The quality factor and line width can be controlled by asymmetric parameters, which are the offset and radius size of the nano round hole. Additionally, adjustable light absorption can be achieved at the quasi-BIC resonance by doping graphene, which corresponds to the preeminent characteristic of graphene of enhancing light absorption. We conclude that the theoretical fitting results for the dissipation rate of the diagonal round holes (DRH) structure with or without graphene are consistent with the simulated quasi-BIC data. The proposed metasurfaces are more feasible and potentially useful compared to other complex nanostructures, as they may contribute to applications such as high-performance graphene-based devices.